3-Methoxytyramine: An independent prognostic biomarker that associates with high-risk disease and poor clinical outcome in neuroblastoma patients. (February 2018) - Verly, I.R.N.; van Kuilenburg, A.B.P.; Abeling, N.G.G.M.; Goorden, S.M.I.; Fiocco, M.; Vaz, F.M.; van Noesel, M.M.; Zwaan, C.M.; Kaspers, G.J.L.; Merks, J.H.M.; Caron, H.N.; Tytgat, G.A.M.
Abstract: Introduction: Prognosis of neuroblastoma patients is very diverse, indicating the need for more accurate prognostic parameters. The excretion of catecholamine metabolites by most neuroblastomas is used for diagnostic purposes, but their correlation with prognosis has hardly been investigated. Therefore, we performed an in-depth analysis of a panel of elevated urinary catecholamine metabolites at diagnosis and their correlation with prognosis. Patients and methods: Retrospective study of eight urinary catecholamine metabolites in a test (n = 96) and validation (n = 205) cohort of patients with neuroblastoma (all stages) at diagnosis. Results: Multivariate analyses, including risk factors such as stage and MYCN amplification, revealed that 3-methoxytyramine (3MT) was an independent risk factor for event-free survival (EFS) and overall survival (OS). Furthermore, only 3MT appeared to be an independent risk factor for both EFS and OS in high-risk patients, which was independent of modern high-risk therapy and immunotherapy. Among high-risk patients, those with elevated 3MT and older than 18 months had an extremely poor prognosis compared to patients with non-elevated 3MT and younger than 18 months (5-year EFS of 14.3% ± 4% and 66.7% ± 18%, respectively, p = 0.001; 5-year OS of 21.8% ± 5% and 87.5% ± 12%, respectively, p < 0.001). Conclusions: Elevated 3MT at diagnosis was associated with high-risk disease and poor prognosis. For high-risk patients, elevated 3MT at diagnosis was the only significant risk factor for EFS and OS. 3MT was also able to identify subgroups of high-risk patients with favourable and extremely poor prognosis. Highlights: 3-Methoxytyramine elevation correlates with poor event-free survival and overall survival. 3MT is an independent risk factor for event-free survival and overall survival. The prognostic value of 3MT surpasses that of MYCN amplification. The prognostic value of 3MT was not affected by any type of modern therapy. Among high-risk patients, 3MT allows identification of ultra-high-risk patients.